Protection of the right to privacy in the practice of the European Court of Human Rights - Mladenov, Marijana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The right to privacy is a fundamental human right and an essential component of the protection of human autonomy and freedom. The development of science and information systems creates various opportunities for interferences with physical and moral integrity of a person. Therefore, it is necessary to determine the precise content of the right to privacy. The European Convention on Human Rights and Fundamental Freedoms guarantees this right under Article 8. The European Court of Human Rights did not precisely define the content of the right to privacy and thereby the applicants could bring different aspects of life into the scope of respect for private life. According to the Court, the concept of privacy and private life includes the following areas of human life: the right to establish and maintain relationships with other human beings, protection of the physical and moral integrity of persons, protection of personal data, change of personal name, various issues related to sexual orientation and transgender. The subject of this paper is referring to previously mentioned spheres of human life in the light of interpretation of Article 8 of the Convention.